Attention-Based Cross-Modal CNN Using Non-Disassembled Files for Malware Classification - Gattu Yaswanth Ram; Dr. Jayavarapu karthik (Utilitas Mathematica, 2025)
Battling the spread of perilous programming renditions relies first upon the order of malware. This paper handles this issue by recommending a new technique utilizing a “Convolutional Neural Network (CNN)”- based model to group malware occasions into families without relying upon dismantled code, thus inclined to botches. Rather, the model purposes non-dismantled paired documents coordinating two modalities: primary entropies and malware pictures. These modalities offer a few points on the information, subsequently further developing order exactness. Highlights from the two modalities are productively coordinated utilizing a cross-modular consideration process, hence diminishing their different limitations. With extraordinary accuracy of 98%, the recommended model is contrasted and customary strategies including "VGG16, CNN, and XGBoost". Alongside embracing the Xception model, which maybe surpasses close to 99% accuracy, troupe methods including Casting a Voting Classifier and Decision Tree are explored to further develop execution more. An easy to understand frontend produced for testing and verification utilizes likewise a Flask system. This sweeping technique increments client availability and security in malware examination notwithstanding malware order accuracy.